First record of a pontoniine shrimp (Caridea, Palaemonidae) in association with a boring bivalve of the genus Spengleria (Bivalvia, Euheterodonta, Gastrochaenidae) - Fransen, C; Van Der Meij, S (Brill Academic Publishers, 2010)
During fieldwork in Raja Ampat, West Papua, Indonesia, in 2007, a pontoniine shrimp, most likely belonging to the genus Anchistus, was collected from a coral boring bivalve of the genus Spengleria. This is the first record of a pontoniine shrimp living in association with a boring bivalve. As it probably concerns a juvenile shrimp, its identity remains unclear. Its affinities with the Indo-West Pacific mollusc-associated genera and with congenerics are discussed.